Evaluasi Program GEMERLAP di Desa Candisari Kecamatan Sambeng: Studi Deskriptif pada Kelompok Tani Holtikultura “Godong Ijo Sejahtera” (Evaluation of GEMERLAP Program in Candisari Village, Sambeng Subdistrict: Descriptive Study of Horticultural Farmers' G - Milla, Anikdatul; Murdiyastuti, Anastasia; A, Anwar (University of Jember, 2019)
AbstractTh is r ese a r ch a ims to e va l ua t e t h e p r o g r a m o f t h e M o v e m e n t to B u ild a V illa g e B a s ed So ciety Ec ono my inC and i s a r i vill ag e, Sa m b e ng s u b d i s t r ict. T h is d esc r i p tive r ese a r ch em p l o y e d a qua litat i ve app r oa c h T h ei n f o r m an ts w e r e d etermi n ed pu r po s ivel y Rese a r ch da ta w e r e c o llected t h r o u g h ob s erv a ti on i n tervie w , an ddo c u me n t a ti o n D a t a w e r e a n a lyzed b y u s i n g i n teractive an a lys i s o f Mi l es an d H ub erm a n w h ich c o n s i s tedo f da ta r e du cti o n da ta p r ese n t a ti o n an d d r a w i n g c on cl u s i o n T o test da ta v a li d it y r ese a r c h ers u s ed s ou r cet r i angu l a ti on T h e t h e o r y u s ed in e va l ua ti n g t h e M o v e me n t to B u ild a V illa g e B a s ed So c i ety Ec ono my w a sW ill i a m N D unn 's e va l ua ti o n t h e o r y B a s ed o n t h e fi nd i n g s , f r o m t h e s ix W i l li a m N D un n cri t eria u s ed toe va l ua te, o n ly t w o w e r e f u lfi l led na mely lev e li n g a n d a c c u r a c y . W h ile t h e o t h er f ou r cri t eria, na melye f fectiv en e s s e f fi c ie n c y ad e q ua c y an d r es p o n s ive n ess w e r e s till poo r T h is c ond ition w a s du e to s e v er a lf a ct o rs na mely t h e l a ck o f o p tim a l e f f o r t o f go v e r n me n t in im p lem en ti n g t h e p r og r a m an d o v e r c o mi n g t h ee p i d emi c s T h is c ond ition h a pp e n ed b e cau s e t h e C a li n a P apa ya p r og r a m w a s no t i n cl u d ed in t h e R o a dM a p o f t h e O f fice o f Fo o d C r op s Pl an t a ti o n a n d H o r tic u lt u r e.Ke y w o r d s p r og r a m e va l ua ti o n G E ME R LAP